Gender, Penghargaan Finansial, Pengakuan Profesional Terhadap Pemilihan Karir Sebagai Profesi Akuntan Pada Mahasiswa Di PT Provinsi Gorontalo - Sendy Ledyandini; Imran Rosman Hambali; Ayu Rakhma Wuryandini (Jambura Accounting Review, 2020)
This research aims to find out The Influence of Gender, Financial Award, and Professional Recognition toward Career Selection as an Accountant on Accounting Students in the College of Gorontalo Province. The research method is a quantitative method. The samples are 74 students of department of accounting in the final year of study. The sampling technique is a simple random sampling. The technique of data analysis uses multiple regression analysis. The findings show that partially variable of gender influences negatively and not significantly on career selection as an accountant, variable of financial award influences positively and significantly on career selection as an accountant, and variable of professional recognition influences positively but not significanlty on career selection as an accountant. Meanwhile, simultaneously variable of gender, financial award, and professional recognition influences positively and significantly on career selection as an accountant. Variable of gender, financial award, and professional recognition are able to explain career selection as an accountant on accounting students as much as 53,5%. While the rest of 46,5% is able to be explained by other variables exclude from this research.